2012
DOI: 10.1016/j.dnarep.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Unique mutational profile associated with a loss of TDG expression in the rectal cancer of a patient with a constitutional PMS2 deficiency

Abstract: Highlights► We characterized the mutator phenotype of a very early onset rectal cancer. ► High frequency of C:G>T:A or G:C>A:T transitions at methylated CpG sites was found. ► A somatic TDG mutation was found associated with TDG expression loss in the tumor. ► 1st in vivo evidence that TDG acts against deleterious 5-methylcytosine deamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…In agreement with this, it has been demonstrated that loss of TDG in tumor cells of mismatch repair deficient patients resulted in high number of base substitution mutations providing the first in vivo evidence for the role of TDG in mutation prevention [43]. Altogether, we observed the involvement of TDG-BER in the removal of TET2-generated genotoxic intermediates in a locus specific manner.…”
Section: Impact Of Tet2-induced 5-hmc On Mutagenesissupporting
confidence: 85%
“…In agreement with this, it has been demonstrated that loss of TDG in tumor cells of mismatch repair deficient patients resulted in high number of base substitution mutations providing the first in vivo evidence for the role of TDG in mutation prevention [43]. Altogether, we observed the involvement of TDG-BER in the removal of TET2-generated genotoxic intermediates in a locus specific manner.…”
Section: Impact Of Tet2-induced 5-hmc On Mutagenesissupporting
confidence: 85%
“…Consistent with this hypothesis, TDG deletion in mice is an embryonically lethal outcome (45). This can also explain why only a heterozygous TDG mutation, but no homozygous mutation, has been found in cancer patients (25,26). This mechanism could significantly reduce the risk of tumorigenesis caused by loss of a DNA repair gene.…”
Section: Discussionsupporting
confidence: 58%
“…In the human genome, the TDG gene is located on chromosome 12q24.1. Recently, in a mutational profile study, a heterozygous mutation in the TDG gene was identified in a rectal cancer patient (25,26), suggesting that TDG may function as a tumor suppressor. To examine the mechanism and function of TDG in CRC, we analyzed the effects of TDG on Wnt signaling.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…The spectrum of single-base mutations found in the p53 gene outside of CpG dinucleotides in brain tumors is consistent with cycles of endogenous damage and repair cycles. The T-G mispair formed by hydrolytic deamination of 5-methylcytosine can be repaired by four human glycosylases: UNG2, SMUG1, MBD4, and TDG (Vasovcak et al 2012). Failure to repair the T-G mispair would result in the observed GC to AT transition mutations frequently observed at p53 CpG sites in glioblastoma.…”
Section: Inflammation Dna Damage and Genetic Mutations In Glioblastomamentioning
confidence: 97%